A rare case report of ectopic tooth in submandibular salivary gland's duct - Abdul Jabbar, Omar; Mustafa, Nazih Shaban; Kashmoola, Muhannad Ali H. (International Islamic University Malaysia, 2019)
This case report highlights mandibular tooth in an ectopic position in the floor of the mouth, associated with submandibular salivary gland, which was completely obliterating the Wharton duct. Very few such cases have been reported in the literatures. Since ectopic tooth may lead to pain, discomfort sensation upon mastication, and even infection (sialadenitis), its diagnosis and treatment is essential